Pengaruh Kompetensi Pedagogik Guru terhadap Hasil Belajar Peserta Didik Kelas X Mata Pelajaran Akuntansi Dasar di SMK Islam Wijaya Kusuma - Garnis Putri Sulandari; Windi Megayanti (LITERATUS, 2022)
The purpose of the study was to determine the effect of teacher pedagogic competence on the learning outcomes of students in class X in basic accounting subjects at Wijaya Kusuma Islamic Vocational School. The population of this study were students of class X majoring in Accounting and Institutional Finance (AKL) with a total of 80 students. The number of samples taken as many as 80 students by using a sampling technique that is total sampling. Methods of data collection using observation, questionnaires (questionnaire) and documentation. The results obtained are correlation coefficient of 0.462, indicating that there is a moderate relationship between teacher pedagogic competence and learning outcomes. The coefficient of determination is 21.34% which means that the teacher's pedagogic competence contributes to learning outcomes by 21.34%, while the remaining 78.66% is the contribution of other factors, such as social competence, personality competence and professional competence. The results obtained from testing the hypothesis that the value of tarithmetic > ttable is 4.600 > 1.665. This proves that there is a positive and significant influence of teacher pedagogic competence on the learning outcomes of students of class X basic accounting subjects at Wijaya Kusuma Islamic Vocational School.